Hybrid nanofluid convection and phase change process in an expanded channel under the combined effects of double rotating cylinders and magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2022)
Convective heat transfer and phase changing process are analyzed for flow over facing step in a channel equipped with double rotating circular cylinders and phase change- packed bed (PCM-PB) under magnetic field. The favorable and opposing effects of using magnetic field with rotations on phase change and thermal performance for separated flow in PCM-PB installed system are numerically explored by using the finite element method. Base fluid with hybrid particle loading of 2% solid volume fraction is used. The analysis is performed for various values of rotational Reynolds number (Rew: -1000 and 1000), cylinder sizes (R:0.01 and 0.3), size ratio (SR:0.5 and 2) and Hartmann number (Ha: 0 and 20). When rotations are active, phase change becomes inefficient due to the establishment of the vortices near the PCM-PB zone. Complete phase transition time (tC) depends upon the rotational direction of the cylinders and fluid type. As compared to case at Rew = 0, tC rises up to 175% at Rew = 1000 by using pure fluid while using nanofluid reduces the tC value. The size and size ratio of the cylinders are highly influential on the vortex size behind the step which affects the phase transition dynamics. There are 185% and 172% variations in the tC values are observed when size and size rations are varied. The case with the PCM + nanofluid gives the highest Nusselt number (Nu) while lowest Nu is obtained when pure fluid without PCM is used. The average Nu rises with larger cylinders for counter clockwise rotations at the highest speed. Magnetic field suppresses the vortices and contributes positively to the phase change process and thermal performance while reduction of tC is up to 74% is obtained at Rew=-1000 by using magnetic field at the highest strength. Proper orthogonal decomposition (POD) is used for fluid and solid temperature reconstruction in the whole computational domain. The model captures the dynamic behavior of phase change and heat transfer under combined effects of double rotations and magnetic field with PCM-PB embedded channel with area expansion. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Backward facing step; Hybrid nanofluid; Phase change dynamics; Double rotating cylinders; Proper orthogonal decomposition